Psychedelic renaissance in healthcare: between the biomedical and the existential - Daniel Laforest (Medical Humanities, 2026)
In this review essay I outline how the current renaissance of psychedelics in mainstream discourses about medicine is spearheaded first and foremost by profit-oriented technomedical initiatives focusing on individual wellness, and how this very situation reinforces a problematic line of demarcation between the psychopharmaceutical approach to mental health, and the more classical approach that relies on intersubjective talk therapy. It will lead me to formulate brief remarks about the unique challenges that this context presents for the field of medical humanities—specifically regarding the status of narratives in therapy and their existential implications.